Diagnostic performance of computed tomography for parathyroid adenoma localization; a systematic review and meta-analysis. Issue 88 (March 2017) - Kluijfhout, Wouter P.; Pasternak, Jesse D.; Beninato, Toni; Drake, Frederick Thurston; Gosnell, Jessica E.; Shen, Wen T.; Duh, Quan-Yang; Allen, Isabel E.; Vriens, Menno R.; de Keizer, Bart; Hope, Thomas A.; Suh, Insoo
Highlights: CT performs well in localizing pathological parathyroid glands. Performance of CT is less in patients with inconclusive ultrasound and sestamibi. Addition of a third contrast phase seems to have little added value. Abstract: Abstract purpose: To perform a systematic review and meta-analysis of the sensitivity and positive predictive value (PPV) of CT for preoperative parathyroid localization in patients with primary hyperparathyroidism (pHPT), and subsequently compare the different protocols and their performance in different patient groups. Materials and methods: We performed a search of the Embase, Pubmed and Cochrane Library databases to identify studies published between January 1, 2000 and March 31, 2016 investigating the diagnostic value of CT for parathyroid localization in patients with biochemical diagnosis of pHPT. Performance of CT was expressed in sensitivity and PPV with pooled proportion using a random-effects model. Factors that could have affected the diagnostic performance were investigated by subgroup analysis. Results: Thirty-four studies evaluating a total of 2563 patients with non-familial pHPT who underwent CT localization and surgical resection were included. Overall pooled sensitivity of CT for localization of the pathological parathyroid(s) to the correct quadrant was 73% (95% CI: 69–78%), which increased to 81% (95% CI: 75–87%) for lateralization to the correct side. Subgroup analysis based on the number of contrast phases showed that adding a second contrast phase raises sensitivity from 71% (95% CI: 61–80%) to 76% (95% CI: 71–87%), and that adding a third phase resulted in a more modest additional increase in performance with a sensitivity of 80% (95% CI: 74–86%). Conclusion: CT performs well in localizing pathological glands in patients with pHPT. A protocol with two contrast phases seems to offer a good balance of acceptable performance with limitation of radiation exposure.